Prevalence Paramphistomum spp. In Animal Qurban In Lima Puluh City District - Engki Zelpina; Prima Silvia Noor; Ramond Siregar; Sujatmiko Sujatmiko; Devi Kusmira; Ulva Mochtar Lutfi; Yurni Sari Amir Amir; Delli Lefiana; Reni Novia; Suliha Suliha; Latisar Latisar (Journal of Applied Veterinary Science And Technology, 2023)
Background: Paramphistomum spp. is a genus of parasitic flatworms belonging to the Digenea tribe in Trematoda. Paramphistomum spp. young worms have a predilection in the small intestine, while adults Paramphistomum spp. predilection in the rumen and reticulum. Infestation from the presence of Paramphistomum spp. in sacrificial animals can be detrimental to buyers and sellers of sacrificial animals. Purpose: This study aims to determine the presence of Paramphistomum spp in the rumen of sacrificial animals in Fifty Kota District. Methods: This research was conducted in July 2022 with 116 samples. Sampling was randomly carried out at the qurban animal slaughter location in Limapuluh Kota Regency. The post-mortem examination was carried out on the rumen of sacrificial animals with systematic inspection and incision to see Paramphistomum spp. infestation. If Paramphistomum spp. worms are found. Then, the sacrificial animal is declared positive if it is not found otherwise negative. Results: The results showed the prevalence of Paramphistomum spp. worm infestation in the rumen of sacrificial animals in Limapuluh District was 24.14%. Conclusion: The highest prevalence of Parampistomum spp. was in the type of cow sacrifice animal, with a prevalence of 96.43%. Based on the sex of the female qurban animal, it was higher with a prevalence of 85.71%, while based on age, the highest prevalence was in qurban animals aged 2.5 years with a prevalence of 31.25%.